A fluorescent biosensor reveals conformational changes in human immunoglobulin E Fc: Implications for mechanisms of receptor binding, inhibition, and allergen recognition - Hunt, J.; Keeble, A.; Dale, R.; Corbett, Melissa; Beavil, R.; Levitt, J.; Swann, M.; Suhling, K.; Ameer-Beg, S.; Sutton, B.; Beavil, A. (American Society for Biochemistry and Molecular Biology, Inc., 2012)
IgE binding to its high affinity receptor Fc?RI on mast cells and basophils is a key step in the mechanism of allergic disease and a target for therapeutic intervention. Early indications that IgE adopts a bent structure in solution have been confirmed by recent x-ray crystallographic studies of IgEFc, which further showed that the bend, contrary to expectation, is enhanced in the crystal structure of the complex with receptor. To investigate the structure of IgEFc and its conformational changes that accompany receptor binding in solution, we created a Förster resonance energy transfer (FRET) biosensor using biologically encoded fluorescent proteins fused to the N- and C-terminal IgEFc domains (C?2 and C?4, respectively) together with the theoretical basis for quantitating its behavior. This revealed not only that the IgEFc exists in a bent conformation in solution but also that the bend is indeed enhanced upon Fc?RI binding. No change in the degree of bending was seen upon binding to the B cell receptor for IgE, CD23 (Fc?RII), but in contrast, binding of the anti-IgE therapeutic antibody omalizumab decreases the extent of the bend, implying a conformational change that opposes Fc?RI engagement. HomoFRET measurements further revealed that the (C?2)2 and (C?4)2 domain pairs behave as rigid units flanking the conformational change in the C?3 domains. Finally, modeling of the accessible conformations of the two Fab arms in Fc?RI-bound IgE revealed a mutual exclusion not seen in IgG and Fab orientations relative to the membrane that may predispose receptor-bound IgE to cross-linking by allergens.